2020
DOI: 10.1007/978-3-030-55807-9_51
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Optimal Route Selection on the Forward Position Solutions of Parallel Mechanisms

Abstract: The forward position solution (FPS) of a parallel mechanism (PM) can be solved according to the sub-kinematic chain (SKC) contained in the PM, and the SKC position solution can be solved based on the sequence of its loops. Therefore, when solving the position, the first loop must be correctly and orderly selected. The optimisation criterion of the first loop proposed for the FPS in this paper can make kinematics modelling and solve efficiently. A symbolic position solution of a three-translation (3T) PM is tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The three-translation PM proposed by authors [13], denoted as 3T-CU, as shown in Figure 1a, consists of a base platform 0, a moving platform 1, and three different branch chains. Among them, the first branch is R 11 //R 21 //C 31 , which is connected to the base platform 0 through the revolute joint R 11 and connected to the moving platform 1 through the cylindrical joint C 31 .…”
Section: Three-translation Pm (3t-cu)mentioning
confidence: 99%
“…The three-translation PM proposed by authors [13], denoted as 3T-CU, as shown in Figure 1a, consists of a base platform 0, a moving platform 1, and three different branch chains. Among them, the first branch is R 11 //R 21 //C 31 , which is connected to the base platform 0 through the revolute joint R 11 and connected to the moving platform 1 through the cylindrical joint C 31 .…”
Section: Three-translation Pm (3t-cu)mentioning
confidence: 99%